Penerapan Pendidikan Karakter Gemar Membaca Melalui Program Literasi di Sekolah Dasar - Priasti, Silvia Nur; Suyatno, Suyatno (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to find a model for the application of character education for reading fondness through literacy programs. This research is a type of qualitative research with a case study approach. The research subjects consisted of the principal, teachers, and students at SD Negeri Sidareja 01 Cilacap. In collecting data, researchers used instruments in the form of interview guidelines, observation guidelines, and document analysis guidelines. The data analysis technique used is the interactive data analysis technique of Miles and Huberman which consists of data reduction, data presentation, and conclusion drawing. The results showed that character education for reading fondness through the School Literacy Program at SD Negeri Sidareja 01 was carried out through: 1) The habituation phase which includes reading habit for 10-15 minutes and other activities that can build literacy culture and literacy-friendly physical environment conditioning. 2) The development phase which includes the development of literacy skills through various non-academic activities as well as the promotion of the social and affective environment as a model of literate communication and interaction. 3) The learning phase which includes the implementation of learning using a variety of literacy strategies and making schools a literate academic environment through professional development.